A Robotic Assistance Machine Vision Technique for An Effective Inspection and Analysis - Santosh Kumar Sahoo; B. B. Choudhury (International Journal of Electrical and Computer Engineering (IJECE), 2015)
An Inspection is a study of methods and techniques that can be suitably employed in practical applications. In this paper, a new activity is proposed and analysis framework to facilitate the inspection of an object using machine vision technique in which maximum efficiency can be achieved. By using LABVIEW software and vision builder software the quality of output images such as image compression, image restoration and multimedia streaming are achieved successfully. So the proposed design makes use of various image processing functions like special filters and classifiers to compute the optimum results. Using smart camera in the inspection system the static as well as the dynamic object is captured in fraction of seconds without any blurs; as a result the optimum image quality without any distortion is obtained for better analysis. The proposed system is very precise, accurate and flexible with reasonable development cost compared to other model. With the aid of an Industrial robotic system with simulation software the object is replaced immediately when the same is rejected by the machine vision model. Apart from this, the proposed model can be implemented for any type of Automation work